Kepentingan Pemerintah dalam Rotasi Jabatan Studi pada Masa Pemerintahan Raidin Pinin Periode 2017-2022 di Kabupaten Aceh Tenggara - Beruh, Martha; Bakar, Muhammad Bin Abu; Muklir, Muklir (Jurnal Transparansi Publik (JTP), 2023)
This research examines the policy of job rotation in Southeast Aceh District (during the Raidin Pinin administration for the 2017-2022 period). The main questions to be answered in this study are the Position Rotation Policy during the 2017-2022 Raidin Pinim Government Period and secondly, Is there an element of political interest in position rotation that occurs in Southeast Aceh District, the theoretical perspective used in this research is structural. This perspective places the power relations of agents with duality structures, namely strata, and mutual influence. the research method used in this research is descriptive qualitative data collection through three stages including observation, interviews, and documentation, the first finding in this study shows that the position rotation that occurred in Southeast Aceh District during the Raidin Pinim government was not necessarily an effort to pay attention to public services but there is an element of political interest. Second, the position rotation carried out by the Southeast Aceh district government cannot be separated from political interests, but the form of political interest that the authors found in the field are personal interest to gain profit, position rotation in a government needs to be carried out because position rotations can also be positive. especially can improve one's performance and can overcome one's boredom at work. The suggestion that the author wants to convey to the Southeast Aceh District government is if the mutation rotation in Southeast Aceh is carried out once every six months or once every three months this is not very good, because this can hamper the opportunity for someone to show their performance.